2005
DOI: 10.1021/ef0502655
|View full text |Cite
|
Sign up to set email alerts
|

Novel Process for Recycling Waste Plastics To Fuel Gas Using a Moving-Bed Reactor

Abstract: The conventional pyrolysis of waste plastics, carried out in a tank reactor or kiln, yields fuel oil with a wide boiling range. To improve the economic process of feedstock recycling of waste plastics, a new thermal process for fuel-gas production is proposed. Considering the role of sand as an effective heating medium and by using a reactor structure for suitably controlling the reaction temperature and reaction time, a new type of reactor equipped with a screw conveyor has been developed; this reactor is ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 14 publications
2
36
0
1
Order By: Relevance
“…The thermal decomposition of polymers also involves the formation of volatile species within a highly viscous polymeric matrix. An important factor in the formation of gaseous product is the control of the reaction environment in terms of the components in each phase [4].…”
Section: Methodsmentioning
confidence: 99%
“…The thermal decomposition of polymers also involves the formation of volatile species within a highly viscous polymeric matrix. An important factor in the formation of gaseous product is the control of the reaction environment in terms of the components in each phase [4].…”
Section: Methodsmentioning
confidence: 99%
“…The dissolution of PS wastes has been studied but focused on the thermal recycling (pyrolysis) [36]. With this aim, Zhang et al [37] proposed the use of biodiesel as a solvent to obtain a solution with a high specific heat; Kodera et al [38] developed a bench scale process to combine PS and the solvents derived from the pyrolysis of their own wastes; Karaduman et al [39] studied the thermal degradation of PS in aliphatic, cyclic and aromatic solvents. And recently, Kim et al [40] employed automobile lubricating oil wastes as solvent to swell PS wastes observing improved heat transfer.…”
Section: Polystyrene Recyclingmentioning
confidence: 99%
“…Table 10 summarizes the compositions of municipal wastes in Japan and the properties of RDF [36]. A specification guideline of RDF is shown in a technical specification document of the Japanese Industrial Standard as shown in Table 11 [38]. Typical dimension of RDF briquettes is 10 -50 mm diameter and 10 -100 mm length.…”
Section: Refuse-derived Solid Fuelmentioning
confidence: 99%